2001
DOI: 10.1002/app.2271
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial adhesion reaction of polyethylene and starch blends using maleated polyethylene reactive compatibilizer

Abstract: The interfacial reaction of the polyethylene (PE)/starch blend system containing the reactive compatibilizer maleated polyethylene (m-PE) was directly characterized by Fourier transform infrared (FTIR) spectroscopy. A significant amount of anhydride groups on m-PE existed as hydrolyzed forms, resulting in a large amount of carboxyl groups. Using a vacuum-heating-cell designed in the laboratory, the carboxyl groups were successfully transformed into the dehydrolyzed state (i.e., anhydride group). This result en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 29 publications
(23 reference statements)
3
19
0
Order By: Relevance
“…The combination of hydrophobic LLDPE and hydrophilic soya powder resulted in phase separation of the blends. This result is in agreement with various studies on starch and polyolefins [8–10].…”
Section: Resultssupporting
confidence: 94%
“…The combination of hydrophobic LLDPE and hydrophilic soya powder resulted in phase separation of the blends. This result is in agreement with various studies on starch and polyolefins [8–10].…”
Section: Resultssupporting
confidence: 94%
“…Figure 3 shows the result of the effect of TPSS loading on the tensile properties of LDPE=TPSS blends. From Figure 3A, both compatibilized and uncompatibilized The reduction in the tensile strength for the uncompatibilized LDPE=TPSS blends has been reported by other workers [7] , and it is due to the incompatibility between the two materials. LDPE is a hydrophobic material, whereas TPSS is a hydrophilic material.…”
Section: Resultsmentioning
confidence: 72%
“…In most cases the major component of the blends forms the matrix, whereas the minor component forms the disperse phase [7,10] . In this LDPE=TPSS blends LDPE is the matrix, while TPSS is the disperse phase.…”
Section: Surface Fracture Morphology Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Infrared spectroscopy revealed that the anhydride in the master batch was either in the form of maleic acid (peak at ~1710 cm -1 ) or as an ester (peak at ~1740 cm -1 ). 25 Consequently, at least parts of MaPE had connected to PVP with hydrogen bonds through the maleic acid hydroxyl groups. The density of pure montmorillonite is 2608 kg/m 3 .…”
Section: Introductionmentioning
confidence: 99%